Profile of Late Adolescent Performance of Papua in Persipura U-21 Athlete Selection - Leonardo Lubis; Rizki Perdana; Ambrosius Purba; Daniel Womsiwor (Global Medical & Health Communication (GMHC), 2018)
The enthusiasm of the people of Papua for football is in harmony with the emerging numbers of talented football athletes from Papua. It reflected in the selection of athletes football Persipura U-21 (aged 21 years and under) for the late adolescent. This study aims to determine the performance profile of late adolescents of Papua at the selection of Persipura U-21 football athletes. The result can be a material of strategic evaluation for improving the achievements of football sport in Papua. A descriptive study with the cross-sectional design conducted on total samples of 97 late adolescents (ages 16–21 years) of men from all provinces of Papua on Persipura U-21 January 2016 selection. Performance data consisted of body mass index (BMI), subcutaneous fat, cardiorespiratory fitness, anaerobic capacity, muscle endurance, flexibility, power, strength, balance, reaction time, and concentration levels. The results showed that all subjects were in healthy condition and most subjects (85%) had normal BMI. Physical characteristics of subcutaneous fat showed most of the subjects were lacking in the triceps (83%) and supraciliary (58%) fat. The basic physical ability for soccer is in good category whereas cognitive ability is in the less category. The research conclusions indicate the urgency to improve basic physical components of the athlete through a well-scaled and well-programmed exercise plan, as well as mental and cognitive development to improve athlete performance. PROFIL PERFORMA REMAJA AKHIR PAPUA PADA SELEKSI ATLET SEPAK BOLA PERSIPURA U-21Antusiasme masyarakat Papua terhadap olahraga sepak bola selaras dengan munculnya banyak atlet sepak bola bertalenta dari Papua. Hal tersebut terlihat pada seleksi atlet sepak bola Persipura U-21 (usia 21 tahun ke bawah) kategori remaja akhir. Penelitian ini bertujuan mengetahui profil performa remaja akhir Papua pada seleksi atlet sepak bola Persipura U-21 sehingga dapat menjadi bahan evaluasi yang strategis dalam meningkatkan prestasi cabang olahraga sepak bola di Papua. Penelitian deskriptif dengan desain potong lintang dilakukan terhadap seluruh sampel berjumlah 97 remaja akhir (usia 16–21 tahun) laki-laki dari seluruh provinsi Papua pada seleksi Persipura U-21 Januari 2016. Data performa terdiri atas indeks massa tubuh (IMT), lemak bawah kulit, ketahanan jantung paru, kapasitas anaerobik, daya tahan otot, kelentukan, daya ledak, kekuatan, keseimbangan, kecepatan reaksi, serta tingkat konsentrasi. Hasil penelitian menunjukkan bahwa seluruh subjek berada dalam kondisi sehat dan sebagian besar subjek (85%) memiliki IMT yang normal. Karakteristik fisik lemak bawah kulit menunjukkan sebagian besar subjek adalah kurang pada bagian trisep (83%) dan suprailiaka (58%). Kemampuan fisik dasar untuk sepak bola berada pada kategori baik, sedangkan kemampuan kognitif dalam kategori kurang. Simpulan penelitian menunjukkan perlu perbaikan komponen fisik dasar atlet melalui perencanaan latihan yang terukur dan terprogram dengan baik, serta pembinaan mental dan kognitif untuk peningkatan performa atlet.